2023
DOI: 10.1002/adfm.202301319
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Switchable Passive Radiative Cooling Smart Windows with Synergistic Optical Modulation

Abstract: Switchable passive radiative cooling (PRC) smart windows can modulate sunlight transmission and spontaneously emit heat to outer space through atmospheric transparent window, presenting great potential in building energy conservation. However, realizing stable and on‐demand control of the cooling efficiency for PRC materials is still challenging. Herein, an electro‐controlled polymer‐dispersed liquid crystal (PDLC) smart window showing PRC property is designed and prepared by adding mid‐infrared emitting react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 61 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Various electrochromic devices commonly employed in smart windows utilize selective modulation in the visible‐NIR range. [ 10–13 ] However, they often rely on complex composite materials and require electrical control, leading to intricate structures and typically slow operation periods ranging from seconds to minutes. In contrast, TlSe, a single nanomaterial, is well‐suited for use in nanodevices and possesses inherent dual‐band selectivity without the need for an additional fabrication process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Various electrochromic devices commonly employed in smart windows utilize selective modulation in the visible‐NIR range. [ 10–13 ] However, they often rely on complex composite materials and require electrical control, leading to intricate structures and typically slow operation periods ranging from seconds to minutes. In contrast, TlSe, a single nanomaterial, is well‐suited for use in nanodevices and possesses inherent dual‐band selectivity without the need for an additional fabrication process.…”
Section: Discussionmentioning
confidence: 99%
“…Since smart windows typically require high transmission contrast, recently reported EC devices have demonstrated high modulation depths, approaching ≈99% at specific wavelengths. [ 86 ] However, their operation speeds typically fall in the range of seconds to tens of seconds, [ 10–13,85 ] making them less suitable for high‐speed processing of optical information signals. Furthermore, the fabrication of EC devices necessitates the integration of multiple components and most EC layers involve the integration of NIR‐active and visible‐active components to achieve dual‐band modulation, adding complexity to device structure and fabrication.…”
Section: Comparison With Other Dual‐band Modulation Technologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thermochromic smart windows can automatically control solar radiation according to the ambient temperature. 90–94 Smart windows with a radiative cooling effect have improved temperature regulation capabilities. Based on the phase transition properties of poly( N -isopropylacrylamide) (pNIPAm), Lin et al developed a solar and thermal regulatory thermochromic window, as shown in Fig.…”
Section: Application Of Radiative Coolingmentioning
confidence: 99%